2012
DOI: 10.1093/glycob/cws160
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced appearance of the selectin ligand sLeX in herpes simplex virus type 1-infected T-cells: Involvement of host and viral factors

Abstract: Circulating leukocytes that express selectin ligands such as the carbohydrate epitope sialyl Lewis X (sLeX) may interact with endothelial selectins, resulting in transmigration of the leukocyte across the endothelial wall to adjacent tissue. Due to the potential of selectin-ligand interactions as targets in viral pathogenesis, we aimed at determining whether herpes simplex virus type 1 (HSV1) is able to induce the appearance of sLeX at the surface of infected leukocytes. We found that HSV1 infection of a T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…By analogy to previously reported abilities of several viruses to modify ECM composition of the host cells to favor their own dissemination and/or immune escape [6264], one might speculate that the chronic infection by HTLV modulates the cell surface glycan pattern [65]. We showed that terminal β-galactoside glycosylation density is inversely correlated with the ability of infected cells to promote contact-dependent pDC IFN-I production.…”
Section: Discussionsupporting
confidence: 78%
“…By analogy to previously reported abilities of several viruses to modify ECM composition of the host cells to favor their own dissemination and/or immune escape [6264], one might speculate that the chronic infection by HTLV modulates the cell surface glycan pattern [65]. We showed that terminal β-galactoside glycosylation density is inversely correlated with the ability of infected cells to promote contact-dependent pDC IFN-I production.…”
Section: Discussionsupporting
confidence: 78%
“…The virus-induced apoptosis of host cells is one of the important mechanisms of viral pathogenesis [22]. Apoptosis is the first line of defense against viral infection in host cells [16]. The host cells quickly start the apoptotic process under the stimulation of viruses and restrict the replication and transmission of viruses by quickly clearing the infected cells [16,22,36].…”
Section: Apoptosis In the Pathogenesis Of Csfvmentioning
confidence: 99%
“…Apoptosis is the first line of defense against viral infection in host cells [16]. The host cells quickly start the apoptotic process under the stimulation of viruses and restrict the replication and transmission of viruses by quickly clearing the infected cells [16,22,36]. During virus infection, apoptosis can be triggered by diverse cellular signals, including the death receptor-mediated extrinsic pathway, the intrinsic mitochondrial pathway, the granzyme B-mediated pathway, and the endoplasmic reticulum stress-mediated pathway.…”
Section: Apoptosis In the Pathogenesis Of Csfvmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study illustrated the proliferation and other malignant properties such as migration and invasion capability of gastric carcinoma cell line can be inhibited by FUT3 gene silencing [ 21 ]. In contrast, we cannot confirm that the sLe x is all synthesized by FUT3, since FUT4, FUT5, FUT6, FUT-9 and FUT7 also have the α(1,3)-fucosyltransferase activity and their function in Lewis antigen synthesis of different tissue has as well been proved [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%